Influence of using kefir grains as a starter culture on soft cheese properties in North Africa - Mona Abdelfattah Ibrahim Hassan Ali; Barakr Abo-Elyazeed Abdelsalam; Hassan Mohammed Sobhy; Moneir Mahmoud Ibrahim Elabd (Cairo : Mona Abdelfattah Ibrahim Hassan Ali, 2018)
Several approaches have been proposed to improve the quality, safety and productivity of Karish cheese. Nowadays, an upsurge of interest in providing suitable starter culture for cheese production has been observed. In addition to improved quality, enhanced microbiological safety and health benefits, starter cultures have the advantage of offering consistent characteristics to the final products, which is important for commerce. Kefir cheese is produced through the use of kefir grains, rather than an additional rennet or acid. Kefir is the product of fermentation of milk with kefir grains. It is described as a symbiotic association between lactic and acetic bacteria and yeast. Kefir grains have been used for centuries in many countries as the natural starter. The part one of study was conducted to evaluate the properties of soft cheese using different levels of kefir starter (1,1.5, and 2%) with different salting methods (dry, brine and dry brine). The first part of this study showed that the best treatment was 1.5% Kefir with brine salting. Therefore, in the part two of study, a trial was carried out to improve the organoleptic properties of Karish cheese using kefir culture (1.5%) as a starter and compare it to rennet or \ and yoghurt starter. Also, the changes in chemical, microbiological and rheological characteristics were evaluated during the storage period. Karish cheese samples produced using kefir, kefir plus rennet or kefir plus yoghurt showed the highest numbers of total count and yeast and mold while, Karish cheese produced using rennet or yoghurt starter had the lowest numbers of total bacterial count and yeast and mold
Thesis (Ph.D.) - Cairo University - Institute of African Research and Studies - Department of Natural Resources
Issued also as CD
Keywords: Chemical; Kariesh cheese; Kefir starter